2012
DOI: 10.1186/1897-4287-10-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel germline MSH2 mutation in lynch syndrome patient surviving multiple cancers

Abstract: Lynch syndrome (LS) individuals are predisposed to a variety of cancers, most commonly colorectal, uterine, urinary tract, ovarian, small bowel, stomach and biliary tract cancers. The risk of extracolonic manifestations appears to be highest in MSH2 mutations carriers.We present a carrier case with a novel MSH2 gene mutation that clearly demonstrates the broad extent of LS phenotypic expression and highlights several important clinical aspects. Current evidence suggests that colorectal tumors from LS patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…Our results suggest that the number of cases with anxiety may be underestimated with the single use of HADS. Moreover, it has been reported that anxiety is present before and after the genetic study [ 22 , 23 ]. Thus, it is indispensable to evaluate systematically and in detail the psychosocial variables during the CGC process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that the number of cases with anxiety may be underestimated with the single use of HADS. Moreover, it has been reported that anxiety is present before and after the genetic study [ 22 , 23 ]. Thus, it is indispensable to evaluate systematically and in detail the psychosocial variables during the CGC process.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is indispensable to evaluate systematically and in detail the psychosocial variables during the CGC process. Hirschberg and collaborators [ 22 ], suggest the evaluation of psychosocial variables during the genetic counseling process in order to refer patients for psychosocial interventions.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Current CRC screening recommendations for LS patients include colonoscopy every 1-2 years beginning at age 20-25 years. 26,27 A recently reported case study suggests optimal colonoscopy interval lies closer to 1 year in individuals with germline MSH2 mutations, 28 confirming that personalizing surveillance programs can decrease disease morbidity.…”
Section: Discussionmentioning
confidence: 86%
“…Current CRC screening recommendations for LS patients include colonoscopy every 1–2 years beginning at age 20–25 years 26,27. A recently reported case study suggests optimal colonoscopy interval lies closer to 1 year in individuals with germline MSH2 mutations,28 confirming that personalizing surveillance programs can decrease disease morbidity. In the current study, our results suggests that by genotyping MLH1 mutation carriers to identify individuals harboring three risk alleles for SNPs rs3802842 and rs16892766 the probability of developing CRC would decrease as a result of undergoing annual colonoscopy from the age of 20 (or earlier if anyone in the family has been diagnosed with CRC before the age of 25).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MSH2 mutations carriers were found to have a cumulative risk of colorectal cancer, independent of gender, based on research of 121 families with LS [9]. More than half of the LS cases were attributed to MSH2 mutations [10,11].…”
Section: Introductionmentioning
confidence: 99%